From human resources to sustainable outcomes: A moderated mediation analysis of creative Engagement and digital transformation in hospitals - Istanti, Enny; Mujanah, Siti; Sumiati, Sumiati (Edelweiss Applied Science and Technology, 2025)
This study examines the influence of Green Human Resource Management (GHRM) on Individual Green Performance (IGP) in public hospitals, emphasizing Creative Process Engagement (CPE) as a mediating mechanism and Digital Transformation (DT) as a moderating factor. Grounded in the Ability–Motivation–Opportunity (AMO) framework and Social Exchange Theory (SET), the research employs a quantitative, cross-sectional design involving healthcare professionals. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess measurement reliability, structural relationships, and mediation and moderation effects. The results indicate that GHRM significantly enhances CPE, which positively affects IGP, confirming CPE’s mediating role in translating green HR practices into sustainable employee performance. However, neither GHRM nor DT directly influences IGP, highlighting the need for synergy between HR initiatives, creative engagement, and digital capabilities. The findings advance theoretical understanding of how HR systems and technological transformation jointly foster environmental sustainability in healthcare organizations. Practically, the study underscores the importance of integrating green HR policies, creative engagement strategies, and digital infrastructure to achieve long-term sustainability goals.